2020
DOI: 10.1101/2020.11.10.20228973
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of SARS-COV-2 nasal antigen test to nasopharyngeal RT-PCR in mildly symptomatic patients

Abstract: IntroductionCOVID 19 has been vastly spreading since December 2019 and the medical teams worldwide are doing their best to limit its spread. In the absence of a vaccine the best way to fight it is by detecting infected cases early and isolate them to prevent its spread. Therefore, a readily available, rapid, and cost-effective test with high specificity and sensitivity for early detection of COVID 19 is required. In this study, we are testing the diagnostic performance of a rapid antigen detection test in mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 29 publications
(55 reference statements)
6
37
0
1
Order By: Relevance
“…In our study, the overall specificity of the antigen test was found to be very high (99.9 %). This is consistent with previous reports, which all showed specificity numbers close to 100 % ( [6] , [7] , [8] , [9] , [10] , [11] , [12] ). False positive results are thus rare.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, the overall specificity of the antigen test was found to be very high (99.9 %). This is consistent with previous reports, which all showed specificity numbers close to 100 % ( [6] , [7] , [8] , [9] , [10] , [11] , [12] ). False positive results are thus rare.…”
Section: Discussionsupporting
confidence: 94%
“…In the samples with ct values below 30, we found the RAT’s sensitivity to be 83.8 %. This is in line with previous studies which also found an association between high viral load (ct values < 30 or viral load > 10 6 copies/ml) and increased sensitivity, with reports ranging from 80.0 % to 98.0 % ( [6] , [7] , [8] , [9] , [10] , [11] , [12] ). This indicates that the majority of infectious cases can be correctly identified with the RAT.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations